Tenis. Ejercicios progresivos para desarrollar tu juego - Torres Luque, Gema; Sánchez Pay, A.; Gago Fuentes, C.; Ros García, J. (Cuadernos de Psicología del Deporte, 2014)
G. Torres Luque, A. Sánchez Pay, C. Gago Fuentes y J. Ros García (2013). Badalona: Paidotribo